Goat production in the Northern Cape: what are the impacts of farmer training? - Burgess, Roberta (Rhodes University, Faculty of Commerce, Investec Business School, 2010)
The main millennium development goal is to eradicate extreme poverty and hunger in the world by 2015. South Africa is one of the countries that signed this pledge at the millennium summit in 2000. The Department of Agriculture, has initiated a number of projects to assist farmers and communities with reaching this goal. In the Northern Cape, the commercialization of goats is one such anchor project. The major activities of this project is to train farmers in applied and appropriate production practices, assist them with accessing markets and supporting them with improved livestock. The main aim of this research was to evaluate whether the project has achieved its outcome and whether this outcome, is having an impact on the livelihoods of the farmers involved in the project. After reviewing the literature on evaluation research and programme evaluation across time, the different paradigms and approaches, participatory methodology was used in this study. A case study approach was applied to evaluate the outcomes and effects of the training received by farmers, as part of the commercialization of goats programme. The results of the study proved that the training received by members of the Campbell Agricultural Co-operative Enterprises, changed their goat production practices. The training also had a secondary impact. Trained farmers were imparting (technology transfer) their acquired knowledge to other members of the co-operative. This appeared very effective as all members of the cooperative were farming more scientifically. These changes to the production practices had a positive impact on the livelihoods of the farmers, as their animals were of a better quality and they were able to sell their animals at different markets and for better prices. This has however not commercialized their farming operations as they are still faced with many challenges. These challenges are the lack of a proper marketing structure, access to financial assistance, proper infrastructure and adequate transport for the animals to mention a few. If the Department of Agriculture and Land Affairs is serious about assisting these farmers to move from the status of "emerging farmer" to "commercial farmer" they will have to look at addressing the problems experienced with financial access and access to adequate and appropriate transport.
Keywords: Northern Cape (South Africa); Animal culture -- South Africa -- Northern Cape -- Management; Animal culture -- Economic aspects -- South Africa -- Northern Cape; Goat farmers -- South Africa -- Northern Cape -- Education